Pressure ulcers in elders and in nonelders: a historical cohort study - Ivanilda Lacerda Pedrosa (Online Brazilian Journal of Nursing, 2014)
Aim: to compare demographical and clinical characteristics of elders and non-elders with pressure ulcers (PU), hospitalized in an Intensive Care Unit (ICU) of a public school hospital in the Brazilian state of Paraíba. Method: this is a historical cohort study, which included 29 patients between the ages of 18 and 94 years, divided into two age groups (≥60 years old = elder; <60 years old = non-elder). Results: 14 individuals were elders (average age 73.8±10.7 years old) and 15 were non-elders (average age 38.3±12.9 years old). Comorbidities and PU in advanced stages were significantly more common among elders (p=0.017 and p=0.010, respectively). Discussion: it is recognized that the number of ulcers, their stage and parts of the body affected by them can influence the evolution of the clinical state of the patient in the ICU, as well as the acute disturbance responsible for the patient’s hospitalization and associated comorbidities. Conclusion: elder patients present significantly more comorbidities and PU in advanced stages than non-elderly patients. Other characteristics here investigated did not show any significant differences based on the age group.